The European Venture Capital and Private Equity country attractiveness indices - Groh, Alexander Peter; von Liechtenstein, Heinrich; Lieser, Karsten (Journal of Corporate Finance, 2010)
We calculate composite indices to compare the attractiveness of 27 European countries for institutional investments into the Venture Capital and Private Equity asset class. To achieve this we use 42 different parameters, and propose an aggregation structure that allows for benchmarking on more granulated levels. The United Kingdom leads our ranking, followed by Ireland, Denmark, Sweden, and Norway. While Germany is slightly above the average European attractiveness level, the scores are rather disappointing for France, Italy, Spain, and Greece. Our analyses reveal that while the UK is similar to the other European countries with respect to many criteria, there are two major differences, which ultimately affect its attractiveness: its investor protection and corporate governance rules, and the size and liquidity of its capital market. The state of the capital market is likewise a proxy for the professionalism of the financial community, for deal flow and exit opportunities. We determine a reasonable correlation between our attractiveness index scores and actual Venture Capital and Private Equity fundraising activities and prove the robustness of our calculations. Our findings across all the European countries suggest that, while investor protection and capital markets are in fact very important determinants for attractiveness, there are numerous other criteria to consider.